2015
DOI: 10.2525/ecb.53.27
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Photosynthetic Response Curves with Internal CO<sub>2</sub> Measured Directly

Abstract: In this study, a system to measure leaf internal CO2 (Ci) was incorporated into an open gas exchange system (LI-COR, Lincoln, NE, USA). The Ci was directly measured with a cup attached to the abaxial surface of sunflower (Helianthus annuus L.) leaves with open stomata while normal CO2 and water vapor exchange through the same section of adaxial surface was simultaneously detected. The potential problems in the system, namely bulk air flow through the leaf, diffusion leaks, and change in the CO2 gradient inside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
(64 reference statements)
2
9
0
Order By: Relevance
“…were estimated as 0.21 ± 0.079 and 0.71 ± 0.13 μmol s –1 , respectively, values that were comparable to those determined for the smaller LI-6400-40 chamber ( Rodeghiero et al , 2007 ; Tominaga and Kawamitsu, 2015 a ), suggesting a similar rate of diffusion leak on a chamber basis. Accounting for the larger chamber interface (i.e.…”
Section: Methodssupporting
confidence: 78%
See 3 more Smart Citations
“…were estimated as 0.21 ± 0.079 and 0.71 ± 0.13 μmol s –1 , respectively, values that were comparable to those determined for the smaller LI-6400-40 chamber ( Rodeghiero et al , 2007 ; Tominaga and Kawamitsu, 2015 a ), suggesting a similar rate of diffusion leak on a chamber basis. Accounting for the larger chamber interface (i.e.…”
Section: Methodssupporting
confidence: 78%
“…For species having a fast assimilation rate, such as sunflower ( Helianthus annuus L.), the gradient is generally too small to affect C i(m) ( Mott and O’Leary, 1984 ; Boyer and Kawamitsu, 2011 ). The small effect observed for sunflower leaves was confirmed recently when a direct-measurement system for C i ( Boyer and Kawamitsu, 2011 ) was incorporated into a commercial open gas-exchange apparatus ( Tominaga and Kawamitsu, 2015 a ). Using a similar system, however, Tominaga and Kawamitsu (2015 b ) demonstrated that C i(c) markedly differed from C i(m) as stomata began to close after abscisic acid (ABA) was applied to this species.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…significantly disturbed when gs was suppressed at pF 3.8 or more (Figures 3(d, h and 5j)). The fluctuation in C i was probably an error problem with the calculation formula (Tominaga & Kawamitsu, 2015a, 2015bTominaga, Shimada & Kawamitsu, 2018).…”
Section: Discussionmentioning
confidence: 99%